American Legal Realism: Research Programme and Policy Impact - Frans L. Leeuw (Utrecht Law Review, 2017)
The article addresses two questions:1. Can Legal Realism be seen as a scientific research programme enabling growth of knowledge? To answer that question, the author uses Lakatos’s  work on the methodology of scientific research programmes as a frame of reference.2. What has been the role of American Legal Realism during the first part of the 20th century in helping to develop and implement the New Deal policy vis-à-vis its scientific work?After outlining some characteristics of American Legal Realism and Lakatos’s concept, the author studies LR from this perspective and concludes that LR can at the maximum be seen as a research programme of a very rudimentary nature with largely only a focus on procedures/methods. Despite this conclusion, LR has been important in stimulating questions in which social science research and law came together. Next, the professor-realist-relationship that helped President Roosevelt to have his New Deal developed and implemented is also discussed. A downside of this ‘professor-realist-advisor-partnership’ may have been that a LR scientific research programme has not been developed. Given the increased visibility of New Legal Realism, the paper finally stresses the relevance of working with scientific research programmes and the importance of being on the alert when linking research to (legal) policies.